2022
DOI: 10.3389/fpsyg.2022.817639
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Stress and the Quality of Life of Nurses in Infectious Disease Departments in China: The Mediating Role of Psychological Resilience

Abstract: AimWe aim to explore the impact of occupational stress on the quality of life of nurses in infectious disease departments and to explore the mediating role of psychological resilience on this impact.BackgroundSudden public health events and the prevalence of infectious diseases give nurses in infectious disease departments a heavy task load and high occupational stress, which can affect their quality of life, and which is closely related to the quality of clinical care they provide. There are few existing stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 60 publications
3
8
0
Order By: Relevance
“…This is in line with previous studies, such as the one conducted by Yan et al [ 53 ] in hospitals specialized in infectious diseases and in infectious disease departments at general hospitals in China from January to July 2021 (during the COVID-19 pandemic), which found that occupational stress had a major impact on nurses’ QoL. This same study [ 53 ] also found that psychological resilience played a partial role in that impact, which is also consistent with our findings. In fact, our study and the one by Yan et al present similar findings despite having been conducted in two substantially different geographical and cultural settings (Portugal and China).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is in line with previous studies, such as the one conducted by Yan et al [ 53 ] in hospitals specialized in infectious diseases and in infectious disease departments at general hospitals in China from January to July 2021 (during the COVID-19 pandemic), which found that occupational stress had a major impact on nurses’ QoL. This same study [ 53 ] also found that psychological resilience played a partial role in that impact, which is also consistent with our findings. In fact, our study and the one by Yan et al present similar findings despite having been conducted in two substantially different geographical and cultural settings (Portugal and China).…”
Section: Discussionsupporting
confidence: 94%
“…Regarding nurses’ QoL during the COVID-19 pandemic, our study identified stress as a factor strongly associated with lower QoL. This is in line with previous studies, such as the one conducted by Yan et al [ 53 ] in hospitals specialized in infectious diseases and in infectious disease departments at general hospitals in China from January to July 2021 (during the COVID-19 pandemic), which found that occupational stress had a major impact on nurses’ QoL. This same study [ 53 ] also found that psychological resilience played a partial role in that impact, which is also consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, when the stress is high, if an individual’s needs, capabilities or resources cannot be excluded or loaded, it will lead to an increase in employee’s job burnout, 90 and a decrease in quality of life. 91 Furthermore, these results showed that developing mutual trust and interdependence among group members through the leadership of manager (especially in case management support such as individualized care, encouragement, and inspiration) or promoting communication and coordination through group member interactions can reduce work stress of subordinates, which in turn will reduce the job burnout of police officers.…”
Section: Discussionmentioning
confidence: 98%
“…Resilience is a multidimensional construct containing three dimensions: strength, optimism, and tenacity (Chen & Liu, 2007). With the rise of positive psychology, psychological resilience has become a hotspot in psychology and nursing research (Yan et al, 2022). Many scholars have confirmed that resilient nurses are better at overcoming obstacles, navigating uncertainties, and withstanding adverse conditions, which enhances their effectiveness and leads to greater success (Jiménez-Fernández et al, 2022).…”
Section: Introductionmentioning
confidence: 99%